Online Transportation Tariff Application (Maxim) In Padang City Revised from Islamic Business Ethics - Efendi, Faisal; Erlanda, Vonny; Candra, Afrikal; Sumarni, Ira; Mardianton, Mardianton; Mulyani, Ridha (Fakultas Syariah IAIN Kerinci, 2024)
The study was overturned by the fact that consumers who have used the maxim online transportation service in the rural city, where the consumer when using the service initially started its rates are changing and not in accordance with the initial booking. However, at the time the consumer has reached the target Maxim tariff rises for reasons given by the driver unknown. This type of research is a field research with the technique of interviewing stakeholders directly related to the issue the author discusses. Next to answer the problem formula, data in analysis with qualitative descriptive techniques. The result, suggests that in the implementation of the existing Maxim apalikation system in the field town, the initial tariff set by the maxim driver is not in line with the initial agreement. Initially before the pickup of consumers, the tariff was written on an application worth Rs 10,000 rupees, after the driver arrived at the customer pickup address, then the driver sent the consumer to the destination. After that, until the initial tariff of Rs 10,000 has changed to Rs 14,000. The Islamic business ethics review of the business behaviour of Maxim companies in Padang City is not in line with the Islamic ethics of business. It is a deceitful thing, which is the price or the price of the first order, when it has arrived.